Analisis Perilaku Konsumen Terhadap Produk Kosmetik Judydoll - Adinda Mutiara Nurul Lintang; Syafikah Wijayanti (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2025)
This study aims to identify the key factors influencing consumer purchasing decisions for Judydoll cosmetic products, focusing on social recommendations and online reviews. Data was collected from 97 respondents, mostly females aged 18-23. The results indicate that social media (69%) is the primary source of information, and factors influencing purchase decisions include product quality, affordable pricing, and attractive packaging. Recommendations from friends/family (57.5%) and online reviews also significantly impact decisions. The majority of consumers are satisfied and intend to repurchase. This study suggests that Judydoll should continue utilizing social media, maintain product quality, and pay attention to pricing and packaging to enhance consumer satisfaction and loyalty.